PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN TATA USAHA SMA NEGERI I BELITANG OKU TIMUR - Ribuwati, Ribuwati (Graduate Program Magister Manajemen Pendidikan, 2018)
Recently, the internal control system implemented in SMA Negeri 1 Belitang OKU Timur has not been strict, therefore many administrative employees do not work in accordance with their duties and responsibilities so the employee performance becomes low. The problem faced is how the influence of the internal control system on the performance of administrative personnel. Data collection techniques were conducted by literature study, observation, interview, documentation and questionnaire. The results of the internal control system have a positive influence on the administrative staff. Internal control system is a management tool for obtaining information, protection and control, then the organizational activity can run well and if there are irregularities can be solved quickly. Headmaster of SMA Negeri 1 Belitang must be more active in applying the internal control system to the administrative staff to improve its performance and the need for punishment for administrative employees who are reluctant to carry out their work so that there will be awareness of mistakes that have been made.